Understanding material text cultures : a multidisciplinary view (Materiale Textkulturen ;, 2016)
Part of an interdisciplinary project whose goal is to shed new light on how writing was conceptualized, materialized, and contextualized in societies without widespread means of mass-producing inscribed objects, thereby contributing to the understanding of the material text cultures privileged by those societies. This volume comprises six studies on material text cultures in different nontypographic societies, from the 3rd-millennium cuneiform textual record of ancient Mesopotamia to the 20th-century Qur'anic boards of northern and central African provenience.